Lego Games in Increasing Creativity in Early Childhood - Ulfia Fitri Yanti; Luluk Mukaromah (JOYCED: Journal of Early Childhood Education, 2025)
This study aims to analyze the role of lego games in improving the creativity of early childhood at RA Nurul Jadid. Creativity is an important aspect in children's growth and development that can be developed through directed play activities. This study uses a qualitative approach with observation, interview and documentation techniques on children's activities in early childhood education institutions, especially the 4-5 year age group. The focus of this study was directed at class A which consisted of 21 students. The results of the study showed that the use of lego was significantly able to stimulate the development of children's creativity, both in terms of physical motoric, cognitive, artistic, and social emotional development. Children are able to create new shapes, think logically, and interact and work together with their peers. Lego media is effectively used as a fun and meaningful learning medium.